Cardiovascular Health at Age 5 Years: Distribution, Determinants, and Association With Neurodevelopment - Climie, Rachel E.; Tafflet, Muriel; Sloten, Thomas van; Lauzon-Guillain, Blandine de; Bernard, Jonathan Y.; Dargent-Molina, Patricia; Plancoulaine, Sabine; Lioret, Sandrine; Jouven, Xavier; Charles, Marie-Alines; Heude, Barbara; Empana, Jean-Philippe (Frontiers in Pediatrics, 2022)
Background. Early childhood may represent an opportune time to commence primordial prevention of cardiovascular disease (CVD, i.e. prevention of risk factors onset) but epidemiological evidence is scarce. We aimed to examine the distribution and parental and early life determinants of ideal cardiovascular health (CVH) in children up to five years and to compare the level of cognitive development between children with and without ideal CVH at age five. Methods.Using data from the EDEN study, a French population-based mother-child cohort study, CVH was examined in children at five years of age based on the American Heart Association CVH metrics (ideal body mass index, physical activity, diet, blood pressure, cholesterol and glucose levels and passive smoking, considered in sensitivity analysis only). Children were categorized as having ideal (5-6 ideal metrics) or non-ideal CVH (<5 ideal metrics). Intelligence quotient (IQ) at age five was assessed using the French version of the Wechsler Preschool and Primary Scale of Intelligence. Results. Among the 566 children (55% boys), only 34% had ideal CVH. In fully adjusted logistic regression, boys compared to girls (OR=1.77, 95% CI1.13-2.78), children with intermediate (1.77, 1.05-2.98) or ideal (2.58, 1.38-4.82) behavioral CVH at age three and children who spent <30 minutes per day watching television (1.91, 1.09-3.34) at age three were more likely to have ideal CVH at age five. At age five, there was a significant 2.98-point difference (95% CI 0.64-5.32) in IQ between children with, compared to those without, ideal biological CVH after adjusting for confounders. Conclusion. This study highlights that only a third of children aged five had ideal CVH, identified modifiable determinants of ideal CVH and is suggestive of an association between CVH and neurodevelopment at a young age.